Answer:
just look at the algebra formula and simplify to get your answer. Remember to use your powers well
(3x² -7x⁴) from (5x² - 3x⁸)
= 5x² - 3x⁸ - (3x² -7x<span>⁴ )
= </span> 5x² - 3x⁸ - 3x² + 7x<span>⁴
= </span>- 3x⁸ + 7x⁴ + 5x² <span>- </span><span>3x²
</span>
= - 3x<span>⁸ </span>+ 7x⁴ + 2x<span>²</span>
Answer and explanation:
The wrong step <u>is changing the sign in step 2</u>
Such that; in step 1 the student had; (x + 6) and (x - 2)
In step 2, the student should have;
x + 6 = 0 and x - 2 = 0 instead of x - 6 = 0 and x + 2 = 0
Step 3, will thus be;
x = -6 and x = 2